THE MANAGEMENT OF ISLAMIC PHILANTHROPIC INSTITUTIONS USING A TOTAL QUALITY MANAGEMENT APPROACH: A CASE IN MAGELANG - Mochammad Nginwanun Likullil Mahamid (Universitas Muhammadiyah Surakarta, 2023)
This article aimed to find out the forms of management of Islamic philanthropic institutions using a total quality management approach in order to improve the quality of institutional services to underprivileged communities, which was the main goal of establishing Islamic philanthropic institutions. Then, the main focus was to review a book entitled “Model Tata Kelola Lembaga Filantropi Islam: Total Quality Management Approach” written by Nurodin Usman, Agus Miswanto, and Subur in 2021. This book raised a theme of discussion regarding the management of philanthropic institutions in Magelang using a total quality management approach as the main objective of writing this article. Therefore, a study unit of analysis was selected to explore the important findings presented in the book's narrative. Furthermore, several reviews from previous books were added, which had almost the same discussion on the management of Islamic philanthropic institutions. The results of this article contained a discussion about the principles in carrying out every management of Islamic philanthropic institutions using a total quality management approach in the case study in Magelang, which was described in the book, especially regarding the advantages and disadvantages of each principle carried out and how to follow up.